تأثير إستراتيجية تمثيل الأدوار على مهارة الكلام لدى طلاب الفصل الثامن في مدرسة التربية الإسلامية المتوسطة كوتو تنجي فندي سيكيك - رحمياتي, رسما; أرشا, فجريانى; ريزال, إيكا; الحسنة, نور (ANWARUL, 2023)
Problems in teaching the Arabic language in the middle school of Islamic education, koto tinggi padang sikik, that the students ability in speaking skill is low and the research quentions are how to use the role-playing strategy on the speaking skill of the students of the eighth class in the middle school of islmic education, kototinggi padang sikek? As for the type of research used by the writer in this research, it is an experimental research, and the method used is a statistical method because the writer is looking for the effect of role-playing strategy on speaking skill. The number of the research community is 48 students, and the writer takes a sample in this thesis in a random way, which is 32 students. Then the research tools are: observation and testing. As for the result of this research, there is an effect of using the role-playing strategy on the speaking skill of eight-grade students in the Islamic Education Secondary School, Koto tinggi padang sinkek. Because the writer found the result of the calculation T from greater than the result of table T, and the difference between them is 2,42. The researcher concluded that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is acceptable.